An Analysis of Students' Critical Thinking Abilities in Solving Problems Social Arithmetics Junior High School - Subekti, Marfilinda Atma Sari; Pitriyana, Sisi (Jurnal Pendidikan Matematika (JPM), 2024)
Critical thinking skills are necessary because Critical thinking is a form of high-level thinking ability that all students must have, especially in learning mathematics. However, students' Critical thinking skills are honed less during the learning process. Teacher efforts to facilitate students to practice Critical thinking skills are indispensable. So that teachers need a picture of the ability to think critically as a reference to train these skills. To that end, the study aims to describe students' thinking skills in solving social arithmetic problems, especially single-interest matters. This type of research is descriptive qualitative research. The subject of this research is PTS students for the odd semester of the 2020/2021 class VII academic year from a state junior high school in Sleman district. The instruments of this research are problem-solving questions as well as observations and interviews. The results of the research show that the three students have high critical thinking abilities because they can fulfill all indicators of critical thinking abilities in solving single-interest problems. Where all indicators of critical thinking abilities can be met by the three students with varied problem-solving processes.